1997
DOI: 10.1111/j.1600-0447.1997.tb09637.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness, physical abuse and burden of care on relatives: a study of acute psychiatric admission patients

Abstract: As mental health care policies increasingly emphasize treatment and care in community settings, there has been concern over the burden that families of mentally ill people might suffer as a result. We conducted a study of the prevalence of abuse faced by relatives of patients admitted during a 6-month period to the acute psychiatric unit of a busy general hospital, who had previously been living with a relative. Patients and their relatives were assessed using semi-structured interview schedules. The experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 17 publications
0
48
2
9
Order By: Relevance
“…Rather, two studies have shown that for patients with severe mental illness living with family increases the risk of engaging in aggressive behavior (Estroff, Zimmer, Lachicotte, & Benoit, 1994;Swanson et al, 2006). Family members are the usual victims of violence by persons with schizophrenia (Arseneault, Moffit, Caspi, & Taylor, 2002;Nordström & Kullgren, 2003;Vaddadi, Soosai, Gilleard, & Adlard, 1997). This often replicated finding suggests that families do provide care to persons with schizophrenia and this increases their risk of becoming victims of violence.…”
Section: Discussionmentioning
confidence: 90%
“…Rather, two studies have shown that for patients with severe mental illness living with family increases the risk of engaging in aggressive behavior (Estroff, Zimmer, Lachicotte, & Benoit, 1994;Swanson et al, 2006). Family members are the usual victims of violence by persons with schizophrenia (Arseneault, Moffit, Caspi, & Taylor, 2002;Nordström & Kullgren, 2003;Vaddadi, Soosai, Gilleard, & Adlard, 1997). This often replicated finding suggests that families do provide care to persons with schizophrenia and this increases their risk of becoming victims of violence.…”
Section: Discussionmentioning
confidence: 90%
“…2 There is also an increased incidence of verbal abuse, threats, temper outbursts and physical aggression towards caregivers of mentally unwell patients. 3 Given the magnitude of services provided and the sacrifices made by family caregivers, the adverse consequences of care-giving have emerged as a serious public health concern. 4,5 Among the numerous psychiatric disorders seen among caregivers, depression was reported to be one of the first symptoms experienced and also the most enduring psychological outcome for this group.…”
Section: Introductionmentioning
confidence: 99%
“…Among one sample of caregiving family members, all of whom reported threats of or actual physical harm, 79% reported significant emotional symptomology of their own (Vaddadi et al, 1997). In one qualitative study a mother of a son with schizophrenia is quoted, "I don't know what other people live like.…”
Section: Health Status Of Family Members Of Mentally Ill Individualsmentioning
confidence: 96%
“…Current heavy alcohol consumption and current cannabis use have also been associated significantly with higher levels of abuse towards caretakers (Vaddadi, Soosai, Gilleard, & Adlard, 1997).…”
Section: Risk For Violent Behaviormentioning
confidence: 99%
See 1 more Smart Citation